A customised cold-water immersion protocol favours one-size-fits-all protocols in improving acute performance recovery. Issue 1 (2nd January 2018) - Zandvoort, Coen S.; de Zwart, Jelmer R.; van Keeken, Brenda L.; Viroux, Patrick J. F.; Tiemessen, Ivo J. H.
Abstract: The purpose of the present study was to investigate whether a customised cold-water immersion (CWIc) protocol was more effective in enhancing acute performance recovery than a one-size-fits-all CWI (CWIs) or active recovery (AR) protocol. On three separate testing days, 10 healthy, physically active, non-smoking males completed the same fatiguing protocol (60 squat jumps and a 2′30″ all-out cycling time-trial) followed by CWIc (12°C, 10–17 min), CWIs (15°C, 10 min) or AR (60 W, 10 min). Outcome measures to assess acute recovery were heart rate variability (HRV) as HRVrecovery, muscle power (MP) as absolute and relative decline, and muscle soreness (MS) at 0 and 24 h. HRVrecovery for CWIc was significantly higher compared to CWIs ( p  = .026, r  = 0.74) and AR ( p  = .000, r  = 0.95). The relative decline in MP after CWIc was significantly lower than after CWIs ( p  = .017, r  = 0.73). MS 0 h and MS 24 h post-intervention were not different after CWIc compared to CWIs and AR ( p  > .05). The findings of the present study demonstrated that CWIc outperforms CWIs and AR in the acute recovery of cardiovascular (HRV) and CWIs in neuromuscular (MP) performance with no differences in MS. To optimise the effects of CWI, contributions of the protocol duration and water temperature should be considered to guarantee an optimal customised dose.